2017
DOI: 10.1038/s41598-017-11572-8
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Concept of Carbonization Degree in Synthesis of Carbon Dots to Achieve Facile Smartphone Based Sensing Platform

Abstract: Direct pyrolysis of citric acid (CA) has been proved to be a facile bottom–up technique for making pristine carbon dots (CD) with homogenous size distribution. However, limited reports are available on systematic optimization of carbonization degree. In this investigation, pyrolysis temperatures between 160 °C and 220 °C were studied, based on CA thermal decomposition path, using various heating durations. The effect of the formation of more carbonized carbon particles (MCCPs), as the major byproduct of this m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 45 publications
1
26
0
Order By: Relevance
“…Also, in comparison with the spectral characteristics of GCDs, the maximum excitation of P2CDs shifted to the blue (318 nm) and the maximum emission wavelength was at 440 nm with a very weak fluorescence intensity. The synthesis procedure of P2CDs must be behind the poor photoluminescent behaviour of these nanoparticles, as proposed in different works [ 40 , 41 ]. Begheri et al [ 42 ] have suggested that during the thermal treatment, along with CDs more carbonized carbon particles (MCCPs) may also be formed as a major by-product, which have quenching effects on the photoluminescence of the CDs.…”
Section: Resultsmentioning
confidence: 99%
“…Also, in comparison with the spectral characteristics of GCDs, the maximum excitation of P2CDs shifted to the blue (318 nm) and the maximum emission wavelength was at 440 nm with a very weak fluorescence intensity. The synthesis procedure of P2CDs must be behind the poor photoluminescent behaviour of these nanoparticles, as proposed in different works [ 40 , 41 ]. Begheri et al [ 42 ] have suggested that during the thermal treatment, along with CDs more carbonized carbon particles (MCCPs) may also be formed as a major by-product, which have quenching effects on the photoluminescence of the CDs.…”
Section: Resultsmentioning
confidence: 99%
“…Variations in heating time and temperature have major effects on the formation and photoluminescence (PL) properties of CDs [35]. Therefore, we synthesized CDs under four different temperature-time conditions: 220-20, 200-30, 180-40, and 160-50.…”
Section: Resultsmentioning
confidence: 99%
“…The highest emission intensity was observed at 350 and 375 nm. Fourier transform infrared (FTIR) spectra in Figure 3c indicated absorption of stretching vibration O–H, C–H, and C–OH groups [35]. To determine the size distribution of CDs dynamic light scattering (DLS) was employed [37, 38, 39, 40].…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of methods, such as laser radiation, [ 156 ] microwave energy, [ 157 ] hydrothermal/solvation techniques [ 158 ] and carbonization techniques, [ 159 ] have been used for the preparation of imaging and diagnostic agents, such as fluorescent aspirin‐based carbon dots (FACDs). [ 160 ] The novel FACDs showed 23% of quantum yield and a fluorescent lifetime of 3.82 ns.…”
Section: Application Of Nanocarbons To Cvdsmentioning
confidence: 99%